2010
DOI: 10.1007/s00421-010-1365-2
|View full text |Cite
|
Sign up to set email alerts
|

Muscle performance during isokinetic concentric and eccentric abduction in subjects with subacromial impingement syndrome

Abstract: Peak torque (PT), total work (TW) and acceleration time (AT) were measured during isokinetic concentric and eccentric abduction of the shoulder in subjects with subacromial impingement syndrome (SIS) and healthy subjects. The SIS group consisted of 27 subjects (33.48 +/- 9.94 years) with unilateral SIS and it was divided into two groups: (1) SIS with the dominant involved side, (2) SIS with the nondominant involved side. The control group consisted of 23 healthy subjects (32.26 +/- 9.04 years). PT, TW and AT w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
0
13
1
1
Order By: Relevance
“…Isokinetic testing has been demonstrated to be reliable and valid to assess the shoulder complex 17 . However, it should be considered that this kind of testing is not specific to a certain muscle 25 , it evaluates the performance of a muscle group in a determined movement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isokinetic testing has been demonstrated to be reliable and valid to assess the shoulder complex 17 . However, it should be considered that this kind of testing is not specific to a certain muscle 25 , it evaluates the performance of a muscle group in a determined movement.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography improves the differential diagnosis for shoulder pain as it has high sensitivity (98.1%) for identifying rotator cuff tears 24 . Other studies also used ultrasonography in the evaluation of patients with SIS 6,11,25 .…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kas gücünde artma hastalık şiddetinde ve ağrılarda azalma sağlamıştır. 24 İzokinetik dinamometre ile omuzun her yö-nüne yaptırdığımız egzersiz programı sonucunda, tüm skorlarda hem tedavi öncesine göre hem de diğer 3 gruba göre daha fazla düzelme olduğunu saptadık. Ayrıca evreler açısından karşılaştırıldığında da en fazla düzelmenin tüm skorlarda izokinetik egzersiz programında olduğunu gördük.…”
Section: Discussionunclassified
“…7,11,22,23,24,26 Two of those studies addressed ankle and provide information about neuromuscular characteristics, 7,22 while the other studies analyzed other joints. 11,23,24,26 van Cingel et al 7 reported that subjects with chronic ankle instability showed prolonged acceleration times for the evertor muscles (concentric action) at 30°/s and 120°/s as well as for the invertor muscles (concentric action) at 120°/s, when compared with control subjects. So, the authors suggested that these findings could be related to the inversion trauma and consequently slower motor nerve conduction velocity of the fibular nerve.…”
Section: Medicalexpress (São Paulo Online) 2017 Aug;4(4):m170404mentioning
confidence: 99%